2019
DOI: 10.1128/aac.02009-18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intranasal Administration of the Recombinant Endolysin SAL200 in a Lethal Murine Staphylococcus aureus Pneumonia Model

Abstract: SAL200 is derived from a phage endolysin and is a novel candidate drug for the treatment of Staphylococcus aureus infection. We investigated the efficacy of the recombinant endolysin SAL200 in a lethal murine pneumonia model. Lethal pneumonia was established by intranasally administering a methicillin-susceptible (Newman) or methicillin-resistant (LAC) S. aureus strain into BALB/c mice. The mice were treated with a single intranasal administration of SAL200 or phosphate-buffered saline at 2 h after S. aureus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…When administered orally, DNDI-0690 was able to effectively clear all parasites from the skin. 32 Another example was observed when evaluating the efficacy of benzoxaborole compounds LSH001 and LSH003 in the same model; topical application of LSH003 was unable to reduce the lesion size progression (and parasite load) whereas oral administration of the drug reduced this load by 50%. The opposite effect was seen for LSH001, which halted lesion size progression upon topical administration whilst lacking activity upon oral administration.…”
Section: The Skin As the Site For Drug Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…When administered orally, DNDI-0690 was able to effectively clear all parasites from the skin. 32 Another example was observed when evaluating the efficacy of benzoxaborole compounds LSH001 and LSH003 in the same model; topical application of LSH003 was unable to reduce the lesion size progression (and parasite load) whereas oral administration of the drug reduced this load by 50%. The opposite effect was seen for LSH001, which halted lesion size progression upon topical administration whilst lacking activity upon oral administration.…”
Section: The Skin As the Site For Drug Activitymentioning
confidence: 96%
“…The experiment aimed to answer three questions: (i) does DNDI-0690 distribute to the skin, (ii) which administration route, topical or oral, is most suitable and, (iii) does pathology impact skin drug distribution. 32 Skin microdialysis and Franz diffusion cell studies revealed that DNDI-0690 permeated poorly into healthy and diseased skin upon topical application of a saturated solution. An oral dose of 50 mg kg −1 instead lead to rapid distribution of protein unbound DNDI-0690 from the blood into the infected dermis as indicated by a ratio of the area under the curve (0 to 6 hours) of free DNDI-0690 in the skin to that in the blood greater than 80%.…”
Section: Drug Development Paradigmmentioning
confidence: 99%
“…The ability of SAL200 to treat MRSA-associated pneumonia in a mouse model has been investigated. The endolysin rescued 95-100% of mice following infection, whereas 40-93% of the control group died following 60 h of infection ( Bae et al, 2019 ). Aquaphor gel was used to incorporate the lysin LysGH15 and apigenin, forming a LysGH15-api-Aquaphor ointment ( Cheng et al, 2018 ).…”
Section: Phage Lysinsmentioning
confidence: 99%
“…The survival rate further increased to 100% when LysGH15 was combined with apigenin, a naturally occurring flavonoid [ 222 ]. In a second study, conducted in 2018, phage-derived endolysin SAL200 was tested in murine SAP, and achieved higher survival, lower bacterial burden, and improved lung histopathology compared to the control group [ 223 ].…”
Section: Alternative Therapeutic Strategiesmentioning
confidence: 99%